The Roman villa at Minster-in-Thanet. Part 5: The Main House, Building 1 - PARFITT, Keith; BOAST, Emma; MOODY, Gerald; PERKINS, Dave (Archaeologia Cantiana, 2008)
Excavations of a winged corridor villa yielded fragments of mosaic and loose tesserae, dumped in the stoking chamber of a hypocaust in the early 3rd century AD.
p. 309-334, 5 fig.
Keywords: Bibliographie par pays, région ou ensemble géographique; Couloir; Hypocauste; Praefurnium; Villa (Minster-in-Thanet, GBR); Minster-in-Thanet